The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/hypertensionaha.115.06736
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Mediates High-Fat Diet Sensitization of Angiotensin II–Elicited Hypertension by Upregulating the Brain Renin–Angiotensin System and Inflammation

Abstract: Obesity is characterized by increased circulating levels of the adipocyte-derived hormone leptin, which can increase sympathetic nerve activity and raise blood pressure. A previous study revealed that rats fed a high fat diet (HFD) have an enhanced hypertensive response to subsequent angiotensin (Ang) II administration that is mediated at least in part by increased activity of brain renin-angiotensin system (RAS) and proinflammatory cytokines (PICs). The present study tested whether leptin mediates this HFD-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 37 publications
5
87
0
Order By: Relevance
“…41 Another study found that high -fat diet elicits augmented hypertensive response to subsequent angiotensin II administration, which is mediated by leptin through upregulation of the central RAAS and proinflammatory cytokines. 42 These findings indicate that sensitization stems from permanent alterations in the brain RAAS and potentiated activation of markers associated with central plasticity which influence the long -term regulation of BP. Understanding the underlying mechanisms may have important implications for preventing and treating hypertension; however, this requires further investigation.…”
Section: Sympathetic Activation In Human Hypertensionmentioning
confidence: 94%
“…41 Another study found that high -fat diet elicits augmented hypertensive response to subsequent angiotensin II administration, which is mediated by leptin through upregulation of the central RAAS and proinflammatory cytokines. 42 These findings indicate that sensitization stems from permanent alterations in the brain RAAS and potentiated activation of markers associated with central plasticity which influence the long -term regulation of BP. Understanding the underlying mechanisms may have important implications for preventing and treating hypertension; however, this requires further investigation.…”
Section: Sympathetic Activation In Human Hypertensionmentioning
confidence: 94%
“…Overall, the study by Xue et al 9 shows an important role for elevated leptin in sensitization to Ang II-induced hypertension, and provides new insight into potential brain sites of action for leptin-RAS interactions. This study expands upon previous work showing the impact of prior exposure to stimuli in eliciting persistent changes in the central nervous system, to contribute to sensitization of the hypertensive response.…”
mentioning
confidence: 88%
“…In this issue of Hypertension , Xue et al 9 build upon this concept by showing that brain leptin-RAS interactions contribute to sensitization of the hypertensive response. In this study, short-term high fat feeding in rats elicited upregulation of central angiotensinergic and proinflammatory pathways in the hypothalamus (Figure), and subsequent sensitization to Ang II-mediated hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations contradict the results of a recent 3.5-year prospective observational study which showed that high plasma omentin concentrations might serve as a biomarker for an enhanced risk of cardiovascular mortality in patients with established or suspected stable coronary artery disease [47]. Leptin, about 20 years after its discovery as the key marker of the amount of energy stores with serum concentrations proportional to body fat mass but also regulated by short-and long-term food deprivation [48,49], is known as an appetite-suppressing hormone with many other regulatory roles and fortunate effects in leptin-deficient humans (for short review see [50] able to enhance the sympathetic nerve activity but also to upregulate the brain renin-angiotensin system during high-fat diet [51].…”
Section: Low-grade Inflammation Of Adipose Tissue: a Major Link To Vamentioning
confidence: 99%